The elliptical noun phrase in English : structure and use - Günther, Christine, 1981- (Routledge studies in Germanic linguistics, 2013)
This book presents a detailed analysis of structural as well as pragmatic aspects underlying the phenomenon of noun ellipsis in English. Here Günther examines the structure of elliptical noun phrases to account for the conditions on noun ellipsis and those on one-insertion, with special emphasis on the (oft-neglected) parallels between the two. She also examines the use of noun ellipsis with adjectives in order to shed light on this under-researched phenomenon, drawing on data from the British National Corpus.